2002
DOI: 10.1037/0735-7044.116.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory-mediated fear-potentiated startle.

Abstract: Recently, R. Richardson, A. Vishney, and J. Lee (1999) reported that ambient odor cues that were previously paired with footshock potentiate the acoustic startle response in rats. The authors of the present study extend those findings by using a discrete 4-s amyl acetate odor paired with footshock to address several parametric issues that might be important for using odorants as conditioned stimuli (CSs) in this paradigm. Amyl acetate (5%) had no significant effect on startle in untrained rats but did potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…The present study investigated the role of the amygdala and the BNST in freezing elicited by an unlearned olfactory stimulus. Several recent studies have used an odor as a conditioned stimulus (CS) in a fear-conditioning paradigm (Otto et al, 1997;Richardson et al, 1999;Paschall and Davis, 2002). It has been shown that olfactory fear conditioning is mediated by the basolateral nucleus of the amygdala (Cousens and Otto, 1998).…”
Section: Role Of the Amygdala In Tmt-induced Freezingmentioning
confidence: 99%
“…The present study investigated the role of the amygdala and the BNST in freezing elicited by an unlearned olfactory stimulus. Several recent studies have used an odor as a conditioned stimulus (CS) in a fear-conditioning paradigm (Otto et al, 1997;Richardson et al, 1999;Paschall and Davis, 2002). It has been shown that olfactory fear conditioning is mediated by the basolateral nucleus of the amygdala (Cousens and Otto, 1998).…”
Section: Role Of the Amygdala In Tmt-induced Freezingmentioning
confidence: 99%
“…These findings are addressed in the Discussion. Overall, the results of both experiments suggest that olfactory cues serve as efficient S1 and S2 stimuli in second-order fear-potentiated startle paradigms when only a small number of first and second-order training trials are presented.Recently, we reported that discrete (4-sec) olfactory cues paired with footshock serve as effective conditioned stimuli (CSs) for potentiating the acoustic startle response in rats using the fear-potentiated startle paradigm (Paschall and Davis 2002). In those studies, amyl acetate (5%) had no significant effect on startle in untrained rats, but potentiated startle in animals receiving 1, 2, 5, or 10 odor-shock pairings.…”
mentioning
confidence: 99%
“…Recently, we reported that discrete (4-sec) olfactory cues paired with footshock serve as effective conditioned stimuli (CSs) for potentiating the acoustic startle response in rats using the fear-potentiated startle paradigm (Paschall and Davis 2002). In those studies, amyl acetate (5%) had no significant effect on startle in untrained rats, but potentiated startle in animals receiving 1, 2, 5, or 10 odor-shock pairings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of nNOS transmission in an aversive learning to odors is still unknown. Recent studies have shown that odors can be associated with foot shock in the Pavlovian fear conditioning paradigm, and the odor-CS acquires aversive valence to induce fear responses, such as freezing and potentiated startle responses (Otto et al 2000;Paschall and Davis 2002;Jones et al 2005). Olfactory fear processing may differ from contextual or auditory/visual fear.…”
mentioning
confidence: 99%